Relation between deletion of chromosome 1p36 and DNA ploidy in breast carcinoma: an interphase cytogenetic study. Issue 2 (April 1996) - Farabegoli, F; Baldini, N; Santini, D; Ceccarelli, C; Taffurelli, M; Treré, D; Derenzini, M
Abstract : Aims —To investigate whether deletion of the 1p36 region of chromosome 1 is independent of DNA ploidy in breast cancer cells. Methods —Preparations of nuclei from 64 fresh primary breast tumours were studied using dual target fluorescence in situ hybridisation (FISH) combining probes specific for the 1q12 (pUC 1.77) and 1p36 (1p-79) regions of chromosome 1. Signals were counted in 100-300 nuclei and the percentage of cells showing fewer p1-79 than pUC 1.77 signals was measured in each sample. DNA ploidy was investigated by cytofluorimetry in 55 tumour samples. Results —Chromosome 1 aberrations were detected in 56 samples. There were fewer p1-79 than pUC 1.77 signals in 53 samples. The 1p36 region was deleted in 11 samples in which a single p1-79 signal was detected; seven of these samples were diploid. Abnormalities were found in 17/24 diploid and 30/31 aneuploid tumours. Conclusions —Chromosome 1 aberrations, including deletion of the 1p36 region, were observed in diploid breast tumours. Deletion of the 1p36 region may be an early event in tumorigenesis. Given the frequency and importance of chromosome 1 aberrations in the biological behaviour of breast tumours, FISH, used in conjunction with cytofluorimetry, may be helpful for determining prognosis in patients with diploid tumours.